Jovens na prática do grafite: trajetórias de invenções e inversões - Santos, Maria Helena dos (2009)
Inserted in the fields of urban studies and of youth, the present dissertation inquired on the meanings that a graffiti group assigns to their practise in the urban space of the São Paulo Metropolis. In order to answer the original question that guided research namely, how a grafitti group establishes relationships with the city spaces and how its members attribute meaning to their action , this study draws on the broad human sciences literature on youth and on the city, having strongly resorted to Michel de Certeau concepts of space, place, and tactics. By means of interviews and of participant observation, the activities of the group called o.p.n.i. were followed in the city of São Paulo from March, 2007 through January, 2009. A brief account of the city space occupation process and of the emergence of graffiti make up the background against which the analysis unfolds the trajectory of the group and of its three members two blacks and one white, aged 23 to 24 years old, dwellers in São Mateus, in the far outskirts of the city. The analysis of the group constitution and of the tactics they resort to in order to face daily space, race, and class discrimination, which they are aware of allowed for eliciting the various meanings of graffiti for them: through graffiting they become conspicuous, keep group ties, survive; they express themselves, protest, denounce inequality, racism, politicians‟ corruption, police violence. By refusing business appealingness, the keen political intent of their various manifestations led them to engaging in community action among youngsters in their neighbourhood. Following them around the city also allowed for acknowledging the way they build subjectivity intertwined with the group‟s consolidation and with doing graffiti, as a means of sustaining a stubborn refusal of constantly imposed subjection. This research also contains a DVD with the documentary accomplished with the group investigated